Anti-inflammatory effects of selected drugs on activated neonatal and adult neutrophils - Craciun, Eugenia Maria; Altfelder, Jan Felix; Kuß, Navina; Pöschl, Johannes; Ruef, Peter (The Scandinavian journal of clinical & laboratory investigation, 2013)
Aim. In view of the central role of granulocytic neutrophils in the context of inflammatory reactions, the present study focuses on anti-inflammatory effects of drugs on activated neutrophils in neonates and adults. Methods. Sixteen blood samples of neonates and adults were investigated in a prospective study. Loss of deformability, morphological changes, and increases in neutrophil elastase were determined as measures of neutrophil activation due to incubation with the pro-inflammatory cytokine interleukin-8. For inhibition experiments, the blood samples were also incubated with the phosphodiesterase inhibitors milrinone and piclamilast, the protease inhibitor urinastatin, ketamine, protein C concentrate, and the nitric oxide donor FK 409. Changes in deformability were investigated with a cell transit analyzer, morphological changes by microscopic observation, and the extent of neutrophil elastase release with an enzyme immunoassay. Results. The drugs milrinone, piclamilast, urinastatin, ketamine, protein C concentrate and FK 409 showed deactivating effects on activated neutrophils in recommended clinical doses. They improved deformability as well as reduced pseudopod formation and the release of neutrophil elastase. The effects on neutrophils did not differ between neonates and adults despite their functional differences. Conclusion. We conclude that these drugs may reduce the inflammatory response and improve microcirculation in neonates and adults during inflammation.